Numerical study of a toxin and antibody interaction inside the cell - Katauskis, Pranas; Malakauskaitė, Silvija (Lietuvos matematikos rinkinys, 2014)
A nonlinear mathematical model decribing toxin penetration into cell from the extracellular domain and its interaction with an antibody placed inside the cell is studied. The protective properties of the antibody against the toxin are investigated numerically choosing the model parameters in case of the well-mixed solution assumption.
Keywords: antibody; toxin; receptor; cell protection